Analysis of Traumatic brain injury related to Kite flying festival - Manish Jaiswal (Romanian Neurosurgery, 2018)
Introduction: Makar Sankranti or Uttarayan is the kite flying festival in India. The festival marks the end of winter and the beginning of summer as the sun moves to the Tropic of Cancer bringing with it longer and warmer days. But it turns into a difficult day for those who are hospitalised after suffering from kite flying related injuries. Aims & Objectives: The objective of this cross sectional study was to review the demographics, causes injury, severity, treatment and outcome of traumatic brain injuries in victims of this kite flying festival who were admitted in department of Neurosurgery on the occasion this year in January. Patients & Methods: A total of 46 traumatic brain injured patients was admitted under Neurosurgery Services that day, out of which 18 cases were related to kite flying related injury. Data of these 18 patients were analysed and outcome were measured at discharge. Result: kite flying festival related neurotrauma increase 39% more emergency admission burden as compared to routine days in neuro-emergency ward. Most common cause of head injury among them was fall from roof. Majority of them had mild head injury. Associated injuries to other part of body were present in 46% patients. Conclusion: Children were most affected due to unsupervised kite flying on roof and road side catching of kites. Depressed fracture was commonest type of traumatic brain injury. Strict attention to safety measures and parental supervision while flying kites can avoid many preventable injuries to life.